Insidensi dan Laju Infeksi Penyakit Busuk Pelepah Jagung (Rhizoctonia Solani) di Desa Waihatu, Kecamatan Kairatu Barat, Kabupaten Seram Bagian Barat - Qhikan Tampubolon; Jogeneis Patty; Wilhelmina Rumahlewang (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2026)
Fronds rot caused by Rhizoctonia solani is one of the main obstacles in corn cultivation because it can significantly reduce productivity. This study aims to analyze the incidence, severity, and infection rate of fronds in corn plants and examine their development patterns during the plant growth phase. The research was carried out in Waihatu Village, West Kairatu District, West Seram Regency in April-May 2025 with a field survey method and a descriptive approach. Observations were made periodically on 115 sample plants (30% of the total population) for seven observations. The variables observed included disease symptoms, disease severity, and infection rate. The results of the study showed that the disease developed progressively with a sigmoid pattern of epidemics. Early symptoms appear at the age of 26 days after implantation (HST) and progress to the generative phase. The severity of the disease increased from 21.83% to 85.99% at the end of observation. The rate of infection shows a fluctuating pattern with significant increases in the late to early generative vegetative phases. The critical phase of disease attack was identified at the age of 40–54 HST. Environmental conditions in the form of high humidity, optimal temperature, and monoculture cultivation systems play an important role in accelerating the development of diseases. This study confirms that the dynamics of the frond rot epidemic are influenced by the interaction between pathogens, hosts, and the environment. The results of the research can be used as a basis for the development of more effective and sustainable time-based disease control strategies in corn cultivation